Antibacterial activity of Cassia alata stems ethanol extract against Staphylococcus aureus - Mar'ie, Ahmad Mahdi; Zamzani, Irfan; Nashihah, Siti (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2022)
Background: Cassia alata leaves, also known as petai cina or gelinggang in Indonesia, are commonly used to treat skin ailments. Objective: The purpose of this study is to test whether stem of C. alata has antibacterial activity against Staphylococcus aureus. Methods: C. alata stems were extracted using an ultrasound-assisted extraction method. For antibacterial activity, disc diffusion was used with extract concentrations of 25%, 50%, 75%, and 100%. Results: The inhibition zones of the ethanol extract of C. alata stems at 25%, 50%, and 75% concentrations were 17.6 mm, 21 mm, and 22.6 mm, respectively, with the highest inhibition zone at 100% concentration at 25 mm. Conclusion: The ethanolic extract of C. alata stems has a strong inhibitory effect on Staphylococcus aureus.